The criminal model in neoliberal financial capitalism - Pegoraro, Juan S. (Universidad Nacional del Litoral, 2021)
Abstract: It is a critical analysis of today’s capitalism with its criminal forms of accumulation and investment and its political practices that make up what is called Financial Neoliberal Capitalism. Its nature is criminal both in its accumulation of money through various forms of organized crime as in its credit investment transformed into capital to obtain an income. It is a process in which many social actors participate and power relations are exercised. Criminal impunity and social immunity are part of the process. This essay is embedded in the tradition of Critical Criminology facing the resurgence in the academic field of a criminological Neopositivism.